OPTIMIZING SERVICE QUALITY MANAGEMENT OF THE BUS RAPID TRANSPORT SYSTEM IN LAGOS USING THE MULTI-CRITERIA DECISION ANALYSIS - Sulaimon Olanrewaju ADEBIYI; Oluwagbenga John AKINRINMADE; Bilqis Bolanle AMOLE (Scientific Journal of Silesian University of Technology. Series Transport)
Evaluation of Bus Rapid Transportation (BRT) based on service quality criteria and customer satisfaction can never be overemphasized due to its derivative, such as optimizing the performance of the transportation industry. Thus, this study employs the multi-criteria decision-making (MCDM) method for the evaluation of service quality and customer satisfaction of the BRT system in Nigeria using the fuzzy analytical hierarchy process (FAHP) and visekriterijumska optimizacija i kompromisno resenje (VIKOR), which are components of multi-criteria optimization and compromise solution to evaluate notable factors responsible for the user’s perspective. Research design is quantitative and analytical in nature through a survey of experts who are users of BRT services. Samples were drawn through a multi-stage sampling procedure and a total of 402 copies of questionnaires were administered to BRT users based on their experience with the system. Hence, VIKOR and FAHP methods are applied to analyse data retrieved from the field on services quality and performance level. The service quality (SERVQUAL) model (a multi-dimensional research instrument designed to capture consumer expectations and perceptions of service) was modified thereby generating six dimensions and thirty-six service criteria for this research. The FAHP method was employed to determine the weights of the decision criteria because there is a need to measure commuters’ perceptions and expectations based on numerical linguistic variables due to the vague, imprecise and complexity related to the nature of services. The criteria weights and responses of the survey analysis (data) related with the BRT are input for the VIKOR method for ranking. As measuring the perception of service quality based on crispy value can often be misleading, hence, the use of the fuzzy MCDM method can give a more realistic measurement. The result of the multi-criteria decision analysis revealed that pricing quality is the most relevant service quality dimension to users’ satisfaction, followed by the empathy quality dimension. The summary of strength and weakness areas of service quality discovered through the research and its managerial implications with recommendations were related to the appropriate authority in charge of the BRT system for improved performance.